Spontaneous Coronary Artery Dissection (SCAD) and a family history of aortic artery dissection, a case series. (14th October 2021) - McGrath-Cadell, L; Hesselson, S; Tarr, I; Iismaa, S E; Bax, M; Junday, K; Dunwoodie, S E; Fatkin, D; Kovacic, J; Muller, D W M; Giannoulatou, E; Graham, R M
Abstract: Background/Introduction: SCAD typically affects women in their fifth or sixth decade with a paucity of cardiovascular risk factors.(1) It is caused by a coronary artery intramural haematoma with or without intimal tear. Resultant luminal occlusion manifests as myocardial ischaemia/infarction or death. There are two published sporadic cases of SCAD who developed iatrogenic aortic dissection with coronary angiography.(2, 3) We are not aware of any SCAD cases with intercurrent or historical spontaneous aortic dissection. There is a published SCAD case with a familial history of aortic dissection, in her mother.(4) None of these cases reported a connective tissue disorder. Methods: We searched our database of 338 SCAD cases, recruited via social media or cardiologist referral, for cases with a family history of aortic dissection. SCAD diagnosis was confirmed by review of coronary angiogram images by an expert interventional cardiologist blinded to the genetic analysis. Genomic DNA was extracted from buccal cells collected using a cheek swab or mouthwash sample. Whole genome sequencing was performed using the Illumina HiSeq X Ten platform with 30x coverage. These data are being analysed for rare variants in genes associated with familial aortopathies or connective tissue disorders (e.g. FBN1, COL3A1, TGFbR-1/2, SMAD3), as well as for novel gene associations with aortic dissection and/or SCAD. Results: We identified 12 cases with a first- or second-degree relative with aortic dissection. Of these SCAD cases, 11 were female whereas 10 of 12 relatives with aortic dissection were male. In one instance, a maternal uncle, but not the index SCAD case, had Marfan's syndrome. Whole genome sequencing has been performed on the 12 SCAD cases, 2 living relatives with aortic dissection and 2 relatives linking the SCAD and aortic dissection cases. Conclusions: Coronary and aortic dissections have serious consequences and in some families there may be a genetic association between the two conditions. Early identification of variant carriers is critical for disease prevention. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): This work was supported in part by grants from the Cardiac Society of Australia and New Zealand, the National Health and Medical Research Council, Australia (APP1161200), the St Vincent's Clinic Foundation, the Catholic Archdiocese of Sydney, Perpetual Philanthropy, NSW Health and SCAD Research Inc. LMC is funded by a University Postgraduate Scholarship through University of NSW and a grant from the Avant Foundation.